Evaluasi dan Perbaikan Desain Antarmuka Pengguna Situs Web SMA Negeri 1 Bangkalan Menggunakan Metode Webuse dan Pendekatan Human Centered Design - Sapriliana Sukmana Putri; Satrio Hadi Wijoyo; Buce Trias Hanggara (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The website has an important function as a useful media for education. SMAN 1 Bangkalan is one of the schools have their own website to provide information. Information obtained such as announcements or the latest news. This study theme is evaluating and improving the user interface of the official website of SMAN 1 Bangkalan. Website Usability Evaluation Tool (WEBUSE) method as an evaluation material that contains a questionnaire. The function of this questionnaire is to see the level of success of a website that suits user needs. Results of the evaluation found a problem about the user interface of the website that still does not provide satisfaction and comfort of its users. Therefore, this research was conducted to improve the website interface design using HCD so that the design is as desired. The results of the usability evaluation of SMAN 1 Bangkalan website have increased the usability value between the old design and the new design improvement. The overall usability value for the website user interface is currently 0.55 which means it's at a moderate level, and the usability evaluation results for the overall design solution are 0.74 which means it's at a good level,